PENGARUH METODE MACRO ROLE PLAYING TERHADAP PERILAKU PROSOSIAL ANAK - Zakila, Winda; Sukardi , Sukardi; Nada Buahana , Baiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Prosocial behavior is an essential ability that needs to be developed in early childhood to enable children to interact positively with their surrounding environment. However, children's prosocial behavior has not yet developed optimally, necessitating an engaging and enjoyable learning method. This study aims to determine the influence of the macro role playing method on the prosocial behavior of group B children at TK Islam Taliwang. This study uses a quantitative approach with an experimental research type using a Static Group Comparison design. The population of this study is all Group B children at TK Islam Taliwang. Sample determination uses a total sampling technique consisting of an experimental class and a static class. Data analysis techniques utilized descriptive statistics and Independent Sample T-Test. The results showed that there was a significant difference in prosocial behavior outcomes between the experimental group and the static group. Therefore, it can be concluded that there is a significant effect of the macro role playing method on the prosocial behavior of Group B children at TK Islam Taliwang.